P95 Assessment of F/HN-pseudotyped Lentivirus as a Clinically Relevant Vector For Lung Gene Therapy. (19th November 2012) - Griesenbach, U; Inoue, M; Meng, C; Farley, R; Chan, M; Newman, NK; Brum, A; You, J; Kerton, A; Shoemark, A; Boyd, AC; Davies, JC; et al.
Abstract : Rational: Our ongoing efforts to improve pulmonary gene transfer thereby enabling gene therapy for the treatment of lung diseases such as cystic fibrosis (CF) has led to the development of a lentiviral vector (SIV) pseudotyped with the Sendai virus envelope proteins F and HN. Objectives: Here, we begin to place this vector onto a translational pathway to the clinic, by addressing some key milestones that have to be achieved. Main results: These include: (1) a single dose produces lung expression for the life-time of the mouse (approximately 2 years), (2) only brief contact time is needed to achieve transduction, (3) repeated daily administration leads to a dose-related increase in gene expression, (4) repeated monthly administration to mouse lower airways is feasible without loss of gene expression, (5) there is no evidence of chronic toxicity during a 2 year study period, (6) F/HN-SIV transduction generates persistent gene expression in human differentiated airway cultures, and human lung slices and transduces freshly obtained primary human airway epithelial cells. Conclusions: The data support F/HN-pseudotyped SIV as a promising vector for pulmonary gene therapy for a number of diseases including CF and we are now undertaking the necessary refinements to progress this vector into clinical trials.